The layout and facades decoration of Huizhou Traditional Houses under the influence of Neo- Confucianism in the 19th century / Zhang Yao and Alice Sabrina Ismail - Yao, Zhang; Ismail, Alice Sabrina (Universiti Teknologi MARA, Perak, 2025)
This paper investigates the relationship between Zhu Xi's neo-Confucianism and the layout and building facade decoration of three 19th-century buildings in Huizhou The aim is to understand the philosophical thought of Neo-Confucianism embodied in Huizhou architectural design. The objective of this study was to provide designers with a new perspective on Huizhou vernacular architecture. Zhu Xi's Neo-Confucianism was the official philosophy of the Yuan, Ming, and Qing dynasties in China. Hongcun Village in Huizhou is Zhu Xi's hometown and a world cultural heritage site. Neo-Confucianism profoundly influenced Huizhou's architectural design. Space syntax was used to analyze the architectural plan. Field investigation, photography, drawing, and literature review were used to analyze the decoration of three Hongchun buildings facades and the design philosophy of Huizhou architecture. The study found that the layout of Huizhou buildings attaches importance to the privacy and tranquillity of the elderly, reflecting filial piety. The decoration of the building facades expressed the three aspects of Neo-Confucianism (filial piety, benevolence and etiquette) through a large number of carved patterns and painted patterns. Neo-Confucianism has influenced the ideology of the Huizhou people. These ideologies are also reflected in the architectural design of Huizhou, and these design methods also influence the lifestyle of the next generation.